Dermatoprotective effects of some plant extracts (genus Ficus) against experimentally induced toxicological insults in rabbits. (November 2015) - Waheed, Muzzamil; Muhammad, Faqir; Javed, Ijaz; Akhtar, Masood; Saleemi, Muhammad Kashif; Khaliq, Tanweer; Awais, Mian Muhammad; Anwar, Muhammad Irfan
Aim: Present study was conducted to evaluate the dermatoprotective effects of plant extracts ( Ficus religiosa, Ficus benghalensis, and Ficus racemosa ) against known irritants such as sodium dodecyl sulfate (SDS), atrazine, and petrol. Methods: The study was conducted in adult male rabbits. Ethanol extracts of plants were obtained through Soxhlet. All irritants and Ficus extracts were topically applied to the backs of rabbits daily for 4 days, while pure ethanol served as control. Skin was examined after 24, 48, and 96 h for erythema. Skin biopsies were taken on 5th day for microscopic examination. Results: Erythema produced by irritants reduced significantly with the simultaneous application of Ficus extracts. The mean ± SEM epidermal thickness (micrometer) with SDS was 45.40 ± 1.89, F. religiosa + SDS was 18.60 ± 0.51, F. benghalensis + SDS was 18.40 ± 0.25, F. racemosa + SDS was 18.80 ± 0.37, and mixture of three Ficus species + SDS was 16.80 ± 0.37. Similar findings were revealed after using plant extracts with atrazine and petrol. The mean ± SEM epidermal layer count for SDS was 3.60 ± 0.25, atrazine was 3.40 ± 0.25, petrol was 3.40 ± 0.25, and ethanol (control) was 1.00 ± 0.20. This count reduced to 1.20 ± 0.20 for three Ficus species + SDS, 1.40 ± 0.25 for Ficus species + atrazine, and 1.40 ± 0.25 for Ficus species + petrol. Conclusion: Ficus species demonstrated the potential to block the dermatotoxic effects of topical irritants and could be used successfully to prevent skin toxicity.